Richard Heinberg (2021) Power: Limits and Prospects for Human Survival - Tweedale, Martin (Journal of Ecohumanism, 2022)
Book Review: Heinberg, Richard, (2021). Power: Limits and Prospects for Human Survival, New Society Press, 2021, 398 pages. US22.99 ISBN 9781550927610